NHC-catalyzed generation of α,β-unsaturated acylazoliums for the enantioselective synthesis of heterocycles and carbocycles - Mondal, S.; Yetra, S. R.; Mukherjee, S.; Biju, A. T. (Accounts of Chemical Research, 2019)
It is reasonable to believe that the chemistry of α,β-unsaturated acylazoliums, catalytically generated through NHCs, will continue to flourish and will lead to amazing results. Future challenges in this area include the applications of this key intermediate in the synthesis of biologically active natural products and drugs.